Isolation And Characterization Of Upregulated Floral Transcripts From Mangosteen (Garcinia Mangostana L.) - Chan, Kam Lock (2008)
Mangosteen (Garcinia mangostana L.) is one of the slowest-growing and longest living tropical fruit trees. Besides long juvenile period, lack of profuse flowering and irregular fruiting during early maturing stage are some of the major problems associated with growing mangosteen as an export fruit or for fruit products. The initiation of flowering process, development and maturation of flower in mangosteen are largely unknown. The understanding of these processes is important to solve some of the problems associated with growing mangosteen as one of the major fruits. Thus, the objectives of this study were to isolate, identify and sequence the mangosteen transcripts that were upregulated in the floral tissues, and study the gene expression and gene copy number of the selected upregulated floral transcripts. In this study, NSTEP method was found to be the best total RNA isolation method for mangosteen tissues. A subtracted cDNA library was constructed to facilitate the isolation of upregulated transcripts from mangosteen flower. Reverse northern screening and sequence analysis revealed that 28.5 % (149/522) of these transcripts were upregulated in mangosteen flower. Among these transcripts, 82 of them were assembled into 30 contigs whereas 67 were singletons. A total of 63.9 % of these unigenes had non-signifancant matches to sequences in the non-redundant protein database in GenBank, 19.6 % had significant matches to unknown proteins and the remaining 16.5 % had putative functions that were further classified into six categories according to their biological functions. A total of three transcripts were selected for further characterization by real time reverse-transcription polymerase chain reaction and southern hybridization analysis. They were GmAGmbp (protein with GATA-type zinc finger domain), GmHsa32 (phosphosulfolatate synthase related protein) and GmbZIP (bZIP transcription factor). The 3’ untranslated region (UTR) of these three transcripts were isolated from a cDNA library constructed using flower of 0.5-1.0 cm. All of these transcripts were verified to be expressed predominantly in the mangosteen flower tissue. GmAGmbp and GmHsa32 were found to be single copy genes in the mangosteen genome. The subtracted cDNAs isolated in this study might be used as expression markers for crop improvement in the future. However, further characterization of expression patterns and functional analyses are required to gather more valuable information on how these transcripts function during the flowering process.